So close yet so far: Island connectivity and ecotourism development in central Mediterranean islands. Issue 1 (March 2021) - Agius, Karl; Theuma, Nadia; Deidun, Alan
Graphical abstract: Highlights: Inadequate connectivity services impact ecotourism development on islands. Distinction of islands promotes island-hopping mitigating connectivity handicaps. Inter-island links can boost ecotourism across the central Mediterranean region. Insularity and remoteness are beneficial for ecotourism development on islands. Mega projects to improve connectivity may lower ecotourism potential of islands. Abstract: Air and sea transport is crucial to link islands with each other and with mainland. In the case of archipelagos, connectivity is based on the hub and spoke network model and is influenced by layering and dominance/subordination relationships. This paper is based on fieldwork in nine islands in the central Mediterranean region that straddle the Malta-Italy border. Whereas some stakeholders consider limitations in connectivity, including high fare prices, low frequency, seasonality, monopoly and lack of stability in agreements with respect to services to be a challenge, other stakeholders consider this as an opportunity for ecotourism development especially on the smaller and most remote islands within archipelagos. Inter-island connectivity is considered as beneficial to boost ecotourism potential and competitiveness (especially on solitary or remote islands) due to different characteristics of islands thus promoting island-hopping. Whereas several measures (including mega-projects) have been proposed or are being studied to mitigate connectivity issues, such projects have raised concern on their environmental impact, possibly resulting in lowering the ecotourism potential of such islands. Therefore, in the context of ecotourism, emphasis needs to be made on improving existing or discontinued connectivity services as well as infrastructure with limited environmental impact.